Organization of the human skeletal myosin heavy chain gene cluster. - Yoon, S J (1992)
Myosin is an important structural and enzymatic component of skeletal muscle. Multiple myosin isoforms are encoded by a multigene family and are expressed in different developmental stages and fiber types. In humans and mice, skeletal myosin heavy chain (MYH) genes are clustered on a single chromosome (17p and 11, respectively). Since the structural organization of the gene cluster may affect its expression as well as shed light on MYH genetic alterations, a physical map of the human MYH gene cluster was constructed. Nine yeast artificial chromosomes containing MYH genes were isolated and used to construct a contiguous set (contig) of overlapping yeast artificial chromosomes. This contig encompasses a genetic marker mapped to 17p13.1. Six MYH genes were located within a 500-kilobase segment of human DNA. The order of the genes within this cluster does not correspond to the developmental pattern of expression of individual members.